Regional heterogeneity of elastin and collagen gene expression in intralobar arteries in response to hypoxic pulmonary hypertension as demonstrated by in situ hybridization. - Prosser, I. W. (1989)
In situ hybridization was used to determine the morphologic distribution of tropoelastin and alpha 1(I) procollagen mRNA expression in elastic intralobar arteries from neonatal calves with hypoxic pulmonary hypertension induced by a 15-day exposure to a simulated altitude of 1500 m. In vessels from normotensive control animals, low levels of hybridizable tropoelastin mRNA were detected in smooth muscle cells (SMC) of the inner media associated with large elastic lamellae. Compared to control arteries, vessels from hypertensive animals demonstrated a markedly different pattern of hybridization. In these arteries, strong hybridization signals for tropoelastin mRNA were seen in SMC lying between the elastic lamellae of the outer media, and the density of labeling associated with these medial cells decreased progressively toward the lumen. Endothelial and adventitial cells in both control and hypertensive arteries were negative for tropoelastin mRNA. Type I procollagen mRNA was dispersed through the media of control arteries, and in hypertensive calves, the hybridization signal was more intense and was unevenly distributed through the media similarly to that for tropoelastin mRNA. Adventitial cells were strongly positive for procollagen mRNA, and the signal was equally intense for both control and hypertensive arteries. Cells that had no detectable tropoelastin mRNA were noted in the outer media of both control and hypertensive vessels. These cells occurred as broad circumferential bands in the normotensive artery and as nodular foci in the hypertensive artery. Immunocytochemical studies with antibodies to smooth muscle specific actin, desmin, and vimentin demonstrated that cells within these foci, as well as tropoelastin mRNA-positive cells, were SMC. These studies demonstrate that expression of tropoelastin and procollagen mRNA was differentially stimulated by pulmonary hypertension within specific regions and SMC populations of the vascular wall.